After the fire - Hill, Will, 1979- (Naperville, Illinois : Sourcebooks Fire, 2018)
Moonbeam, seventeen, survives a devastating confrontation between government forces and the cult she grew up in, but will need a lot of help to heal mentally, emotionally, and physically.
"Originally published in 2017 in the United Kingdom by Usborne Publishing, Ltd., an imprint of Usborne House."
850L
Keywords: Cults -- Juvenile fiction; Survival -- Juvenile fiction; Hospital care -- Juvenile fiction; Psychology -- Juvenile fiction; Thrillers (Fiction); Psychological fiction